Using Hands-on Experiences Including Various Forms of ARTS to Increase Ninth-Grade Female Students’ Interest in STEM - Hui Fang Huang Su; Jia Borror; Teri Williams (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: The research aims to increase interest and a greater awareness of STEM fields among female minority students by providing hands-on STEM-infused workshops incorporating the arts as a central theme. Methodology: The research methodology involved conducting workshops for thirty-seven female students, primarily from low socioeconomic backgrounds, who attended fifteen-hour-long STEM-infused hands-on workshops presented by university professors in the College of Education and the College of Arts and Sciences. Using design computational thinking course intervention, problem based learning approach followed by expert assessment and brief interview survey was adopted. Findings: The study’s results revealed that the 15-week STEM workshops positively impacted the female students’ attitudes toward STEM. In addition, the post-survey results showed a significant increase in their interest in Science, Technology, Engineering, and Mathematics. The data from the results is a promising finding, as it indicates that targeted interventions can effectively increase STEM interest among young female students from underrepresented backgrounds. Implications/Novel Contribution: The implications of this research are significant as it addresses the underrepresentation of female minority students in STEM. In addition, the project enabled students to participate in STEM education inclusively and innovatively. Our aspiration is that through this initiative, students will be able to contribute to promoting diversity and inclusivity within the STEM fields. In addition, the results of this research may provide insights into practical strategies for increasing diversity and inclusivity in STEM fields.